The effect of eight-week interval hypoxic training on serum level of brain-derived neurotrophic factor in active women - Atefe Bagheri; Ali Kazemi (Shahid Beheshti University, 2018)
Purpose: In the present study, the effect of eight weeks of interval hypoxic training (respiratory controlmethod) on the serum level of Brain-derived neurotrophic factor (BDNF) in active women was envestigated.Methods: Fourteen active women were randomly assigned to either the control (n=7) or experimental (n=7)group. The women in the control group performed running interval training under normoxi condition and thesubjects in the experimental group performed runnig interval under hypoxic condition for eight weeks. At thebeginning of the survey and 24 hours after the last training session of the eighth week, the blood samples ofboth groups were collected to determine serum Brain-derived neurotrophic factor level. KolmogorovSmirnov and Leven's test were used to determine normal distribution of data and homogeneity variation ofgroups, respectively. For data analysis, statistical methods including paired and independent-samples t-testat a significance level (p≤0.05) were used.Results: The results showed a significant increase in serum levels of Brain-derived neurotrophic factor aftereight-week interval hypoxic training compared to the interval training. In this regard, the study ofbetweengroups'differences showed that there is significant difference between post-test phase of controland experimental groups (P≤0.036). While, the study of withingroups' differences showed that there was nosignificant difference between pre and post-test phase in control group after eight-week interval training(P=0.157).The difference was significant in experimental group (P≤0.011).Conclusions: The results of the present study suggest interval hypoxic training has an additive effect in thelevels of Brain-derived neurotrophic factor in active women. Thus, it is a good substitution for training ataltitude and blood flow restriction training in terms of time of performing physical activity, cost andimplementation. Therefore, combining sport training with hypoxic and obtaining the desired results in shortertime seems to be an appropriate strategy.